2010
DOI: 10.4103/0972-2327.64643
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke depression: Prevalence and relationship with disability in chronic stroke survivors

Abstract: Objectives:To evaluate (1) the prevalence of operationally defined depressive disorder (ICD-10) in chronic stroke subjects and (2) the relationship of post-stroke depression (PSD) with disability.Design:Cross-sectional, descriptive study.Setting:Neurological rehabilitation unit of a tertiary care university research center.Materials and Methods:Participants were those with first episode of supratentorial stroke of more than 3 months' duration with impaired balance and gait who had been referred for rehabilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 23 publications
4
60
2
3
Order By: Relevance
“…In this present study urban dwellers had higher proportions of PSD compared to rural dwellers; this is similar to earlier work 36 . This could be due to locations where the two centers where this study was conducted are urban and serve mainly urban dwellers, although one of them is a national referral serving the whole country.…”
Section: Discussionsupporting
confidence: 93%
“…In this present study urban dwellers had higher proportions of PSD compared to rural dwellers; this is similar to earlier work 36 . This could be due to locations where the two centers where this study was conducted are urban and serve mainly urban dwellers, although one of them is a national referral serving the whole country.…”
Section: Discussionsupporting
confidence: 93%
“…PSD is a significant health concern being associated with increased disability [8,9], mortality [10], poorer functional outcomes [11], reduced quality of life (QoL) [12,13] and increased use of healthcare services [14]. Previous perceptions from earlier observational studies indicate that the greatest risk for PSD occurs within a few months of stroke onset [5,15,16], although a recent systematic review found the risk was similar (around 30%) in the early, medium and long-term recovery stages [17].…”
Section: Introductionmentioning
confidence: 99%
“…The social, physical and psychological consequences of stroke are devastating [710]. These consequences are described by studies that elaborate Quality of Life(QOL).…”
Section: Introductionmentioning
confidence: 99%